EFFECTIVE APPROACHES TO ENGLISH LANGUAGE INSTRUCTION FOR ELEMENTARY-LEVEL STUDENTS THROUGH HANDS-ON ACTIVITIES - Akbarov Alijon Ikrom ogli, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Currently, the need to master a foreign language is dictated by the modern social order of society,which is due to the growth of intercultural contacts in all spheres of human  activity.  Learning  a  foreign language  at  school begins  in the elementary  grades,  and  from  that  moment  the  whole  learning  process  acquires  a communicative  orientation.  The  methodology  of  teaching  a  foreign  language  in elementary school is still in the formative stage, today the search for effective methods of teaching a foreign language in junior school is actively carried out, which are based on the psychological characteristics of students of this stage.    Information and communication technologies are widely used in the education system,  as  well  as  in  other  industries.  Conducting  classes  with  the  use  of  new pedagogical  technologies  requires  special  intellectual  abilities  from  the  teacher. Education  can  be  transformed  only  when  the  teacher  can  accurately  identify  the interests  of  students,  correctly  direct  them  to  the  path  of  achieving  the  goal.  The teacher's use of interactive methods in his classes contributes to the  development of a real environment of rivalry and cooperation.